Sedentary behaviour, physical activity and cardiometabolic health in highly trained athletes: A systematic review and meta-analysis - Franssen, W. M. A.; Vanbrabant, E.; Cuveele, E.; Ivanova, A.; Franssen, G. H. L. M.; Eijnde, B. O. (European Journal of Sport Science, 2022)
Prolonged periods of sedentary time appear to increase the risk for the development of several chronic conditions and all-cause mortality, even when moderate-to-vigorous physical activity (MVPA) is taken into consideration. However, whether the beneficial health effects of MVPA in highly active individuals remain present when leisure time is spent sedentary remains speculative. Therefore, we systematically evaluated off-training sedentary behaviour and physical activity levels in athletes. Studies were collected from four bibliographic databases (PubMed, Embase, Web of Science and The Cochrane Central Register of Controlled Trials). Studies were eligible for inclusion if they evaluated sedentary behaviour and physical activity levels among athletes. Data from athletes were compared with the general population and pooled using a random-effects model. After deduplication 3104 were identified of which 13 studies met inclusion criteria. Compared to the general population, athletes spent significantly more time in sedentary behaviour (+79 min/day; 95% confidence interval [CI]: [41, 65] min/day; p<0.001). In addition, athlete individuals spent less time in light intensity physical activity (-92 min/day; 95% CI: [-117, -66] min/day; p<0.001) and had increased levels of moderate-to-vigorous intensity physical activity (+62 min/day; 95% CI: [38, 85] min/day; p<0.001) compared to the general population. Athletes exceed the average time spend sedentary per day and make them even more sedentary compared to the general population.